(untitled) (International journal of artificial intelligence, 2025)
Areas for the observation of the impact of water-physical properties of the soil for many years were determined in the overseas and Reclamation expedition. The demonstration of the selection of experimental areas should be in accordance with the natural conditions of the Bukhara region and agricultural activities on irrigation, as well as on expropriated lands. This conclusion V.ArAreas for the observation of the impact of water-physical properties of the soil for many years were determined in the overseas and Reclamation expedition. The demonstration of the selection of experimental areas should be in accordance with the natural conditions of the Bukhara region and agricultural activities on irrigation, as well as on expropriated lands.